Experimental study on the effectiveness of the PCM cooling vest in persons with paraplegia of varying levels. (July 2020) - Mneimneh, Farah; Moussalem, Charbel; Ghaddar, Nesreen; Ghali, Kamel; Omeis, Ibrahim
Abstract: Persons with paraplegia (PA) from thoracic spinal cord injury (T1-T12) are prone to thermal stress during exercise due to impaired thermoregulation. This study evaluates the effectiveness of phase change material (PCM) cooling vests on persons with PA of different levels of injury during exercise in hot exposure. Sixteen participants were recruited and divided to three groups based on injury level; high-thoracic T1-T3, mid-thoracic T4-T8, and low thoracic T9-T12 to perform a 30-min arm-crank exercise at a 30 °C room condition. Two types of PCM vests at melting temperature of 20 °C were tested: i) V1 with PCM covering the trunk of 3.4 kg overall vest mass and ii) V2 with PCM covering chest and upper back of 2.17 kg overall vest mass. High thoracic and low-thoracic groups performed NV and V1 tests; whereas, mid-thoracic group performed NV, V1, and V2 tests. Heart rate, core, and skin temperatures were monitored during 15-min preconditioning, 30-min exercise, and 15-min recovery. In addition, thermal comfort, sensation, skin wettedness, and perceived exertion were recorded during exercise only. The main findings were that the effectiveness of the cooling vest was dependent on injury level and portion of sensate skin of trunk covered by the PCM packets. Rise in core temperature ( Δ T c r ) was reduced significantly for the low-thoracic group during exercise and recovery ( Δ T c r = 0.41 °C, 0.26 °C for NV and V1; respectively, p <0.05). For the mid-thoracic group, both V1 ( p = 0.001) and V2 ( p = 0.008) were effective in reducing Δ T c r compared to the NV test at the end of the recovery period ( 0.74 °C, 0.42 °C, 0.56 °C, for NV, V1 and V2; respectively). For the high-thoracic group, V1 was not effective in reducing core temperature ( p >0.05). For the mid-thoracic group, V2 at 36% lower mass significantly improved thermal comfort (p = 0.0004) compared to the NV test and was as effective compared to V1 in reducing core temperature. Graphical abstract: Image 1 Highlights: 18 participants with thoracic spinal cord injury divided in 3 groups as per injury level. Participants did 30-min arm-crank exercise in 30 °C environment with and without PCM cooling vest. Mid-thoracic group were tested for two PCM placement, covering trunk (V1) or sensate part of it (V2). Drop in core temperature & improved thermal comfort were achieved for mid & high thoracic groups. 36% lower mass V2 was as effective as V1 in reducing core temperature for mid-thoracic group.